2021
DOI: 10.1155/2021/6668490
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Iron Oxide Nanoparticle Functionalized Activated Carbon and Its Applications in Arsenic Adsorption

Abstract: This work reveals the As(V) adsorption behaviors onto iron oxide (Fe3O4) nanoparticles modified activated carbon (AC), originally developed from biochar (BC), as a green adsorbent denoted by FAC. Since FAC has abundant surface functional groups and a desired porous structure that is favorable for the removal of As(V) in contaminated water, FAC has greatly enhanced the As(V) adsorption capacity of the original BC. Various methods were employed to characterize the FAC characteristics and adsorption mechanism, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…No change was observed after the contact time was increased from 120 min to 24 h, hence, all further experiments were conducted with a contact time of 120 min. A similar trend for arsenic adsorption by nanoparticles prepared from rice husk (Pillai et al, 2020) and iron oxide nanoparticles modified activated carbon (Ha et al, 2021) has been observed in previous studies. Adsorption occurs in a short duration, adsorption sites get saturated, and no removal occurs after saturation (Mohan et al, 2019).…”
Section: Effect Of Contact Time and Initial Arsenic Concentrationsupporting
confidence: 89%
“…No change was observed after the contact time was increased from 120 min to 24 h, hence, all further experiments were conducted with a contact time of 120 min. A similar trend for arsenic adsorption by nanoparticles prepared from rice husk (Pillai et al, 2020) and iron oxide nanoparticles modified activated carbon (Ha et al, 2021) has been observed in previous studies. Adsorption occurs in a short duration, adsorption sites get saturated, and no removal occurs after saturation (Mohan et al, 2019).…”
Section: Effect Of Contact Time and Initial Arsenic Concentrationsupporting
confidence: 89%
“…Examples include the use of NZVI, which can destroy chlorinated organic hydrocarbons such as trichloroethylene [12], trichloroethene (TCE) [13][14][15] and dibenzo-p-dioxin [11]; reduce chlorinated ethanes [16]; and remove nitrites [17]. There is great interest in the possibility of using iron oxide nanoparticles to remove pollutants from the environment, e.g., phenol [18], oxyanions, including arsenite, arsenate, chromate, vanadate and phosphate, or remove toxic metal ions, e.g., for the adsorption of lead (II) [19] and arsenic [20][21][22][23][24][25][26]. An example is magnetic iron oxide modified with 1,4,7,10-tetraazacyclododecane (Fe 3 O 4 @SiO 2 -cyclen), which is able to selectively sorb heavy metal ions Cd 2+ , Pb 2+ and Cu 2+ [27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of advanced materials or technologies for the efficient treatment of As wastewater continues to be a global research priority. Various removal methods have been developed and applied to treat the As-contaminated wastewater, such as co-precipitation for the removal of arsenous acid using Fe(III) and Mn oxide, adsorption methods using various adsorbents and minerals, and ion exchange methods [ 4 , 5 , 12 , 13 , 14 ]. Among them, adsorption is widely used because of its technological simplicity, high efficiency, and low secondary pollution risk [ 15 ].…”
Section: Introductionmentioning
confidence: 99%